Negotiating Jerusalem - Segal, Jerome M., 1943- (SUNY series in Israeli studies., 2000)
An in-depth examination of how Jerusalem is seen by both Palestinians and Israeli-Jews, this book is a landmark study of the potential for successfully negotiating the Jerusalem question. It sheds important light on the question "what is Jerusalem?" By showing that the current boundaries are not viewed by either side as sacrosanct, the authors prove that there is room for creative efforts to reach an agreement. Such room may help resolve what is undoubtedly the most difficult issue standing between Israelis and Palestinians